The Ordovician and Silurian conodonts of Japan: Their biostratigraphical and paleobiogeographical significance. (12th August 2018) - Männik, Peep; Maekawa, Takumi; Tanaka, Gengo; Komatsu, Toshifumi; Siveter, David; Williams, Mark; Hints, Olle; Vandenbroucke, Thijs R. A.
Abstract: Conodont‐bearing Ordovician and Silurian rocks have a wide geographical distribution in Japan. They are exposed on Honshu, Shikoku, and Kyushu islands. Two recently studied samples from Gionyama, in Kyushu, yield conodont assemblages of Telychian ( Distomodus sp., Apsidognathus sp. (cf. A. tuberculatus arcticus ), Oulodus cf. rectangulus, Ozarkodina cf. waugoolaensis, Panderodus cf. amplicostatus ) and probably the earliest Sheinwoodian (? Distomodus sp. (cf. D. staurognathoides ), Ozarkodina sp., Oulodus sp., Walliserodus sp. (cf. Walliserodus sp. nov. c Männik), Panderodus sp.) ages, providing further biostratigraphical constraints for the age of the Gionyama Formation in the Kurosegawa Terrane. Most of the conodont taxa identified have wide paleobiogeographical distribution, but probable occurrence of Oulodus rectangulus, Ozarkodina waugoolaensis, and Panderodus amplicostatus suggests a relationship between Australia, the South China paleocontinent, and the Kurosegawa Terrane of 'Proto‐Japan' during the Silurian. These paleogeographic interpretations agree with the existing notions based on rugose corals. Abstract : Two new conodont‐bearing samples from the Gionyama Formation (Gionyama, Kyushu) provide ages of Telychian (possibly the middle part of the stage), and Wenlock (earliest Sheinwoodian). Most of the conodont taxa identified have wide paleobiogeographical distribution, but the probable occurrence of Panderodus amplicostatus might indicate a relationship between the South China paleocontinent and the Kurosegawa Terrane of 'Proto‐Japan' during the Silurian. This paleogeographic interpretation would agree with earlier conclusions based on rugose corals.